Comparison of methods for monitoring residual platelet reactivity after clopidogrel by point-of-care tests on whole blood in high-risk patients - Paniccia, Rita; Antonucci, Emilia; Maggini, Niccolò; Miranda, Marco; Gori, Anna Maria; Marcucci, Rossella; Giusti, Betti; Balzi, Daniela; Prisco, Domenico; Abbate, Rosanna (Thrombosis and haemostasis, 2010)
Cardiovascular events are more frequent in high-risk coronary artery disease (CAD) patients on dual antiplatelet therapy with a residual platelet reactivity (RPR) than in those showing inhibition of ADP-inducible platelet activation. It is known that post-interventional RPR is a clinically important entity confirming it as a risk factor for thrombo-ischaemic events. Multiple electrode platelet aggregometry (MEA) on whole blood has been recently proposed as a rapid tool to evaluate RPR in high-risk CAD patients on clopidogrel therapy. It was the aim of this study to detect RPR in 801 high-risk CAD patients on dual antiplatelet therapy comparing MEA with the VerifyNow P2Y12 assay on whole blood and classical light transmission aggregation (LTA) on platelet-rich plasma. ADP (10 microM) was employed as agonist for MEA and LTA. The prevalence of RPR was 20.6% by MEA, 16.1% by LTA and 30.8% by VerifyNow. MEA showed a significant correlation (rho=0.62, p<0.0001) with VerifyNow and a moderate agreement (k=0.52, p<0.001) with 81.5% of concordant values. A significant correlation was found between MEA and LTA (rho=0.71, p<0.001) with a good agreement (k=0.63, p<0.001) and 88.8% of concordant values. MEA in relation to LTA showed a sensitivity of 80% and a specificity of 91%. MEA might represent a reliable method and valid alternative in comparison with other available platelet function assays. It might help to guide antiplatelet therapy and thus improve clinical outcome of high-risk CAD patients.